Domestic taxes and international trade : some evidence - Keen, Michael; Syed, Murtaza, 1975- (IMF working paper ;, 2006)
The effects on trade performance of corporate taxes and the value-added tax (VAT) continue to excite controversy but have received little empirical attention. This paper uses panel data for OECD countries from 1967 to 2003 to examine the effects of these taxes on export performance, paying particular attention to the potentially complex dynamic effects to which theory points. It finds that increased reliance on VAT revenue tends to be associated with a sharp reduction in net exports, which quickly fades. This may reflect unrelated movements in consumption, and our preferred specifications point to no trade effects of the VAT in either the short or the long run. Our results also point, however, to powerful and complex effects from the corporate tax, the pattern of which is as theory would predict from a source-based tax of this kind. Increases in corporate taxation-whether measured by revenues or the statutory rate-are associated with sharp short-run increases in net exports (consistent with induced capital flows abroad); these are then subsequently and quickly reversed (consistent with increased income from investments abroad), leaving an increase in net exports that converges to zero.